Application of Lab-on-Chip for Detection of Microbial Nucleic Acid in Food and Environment - Yang, Liu; Yi, Wei; Sun, Fangfang; Xu, Mengjiao; Zeng, Zhan; Bi, Xiaoyue; Dong, Jianping; Xie, Yao; Li, Minghui (Frontiers in Microbiology, 2021)
Various diseases caused by food-borne or environmental pathogenic microorganisms have been a persistent threat to public health and global economies. It is necessary to regularly detect microorganisms in food and environment to prevent infection of pathogenic microorganisms. However, most traditional detection methods are expensive, time-consuming, and unfeasible in practice in the absence of sophisticated instruments and trained operators. Point-of-care testing (POCT) can be used to detect microorganisms rapidly on site and greatly improve the efficiency of microbial detection. Lab-on-chip (LOC) is an emerging POCT technology with great potential by integrating most of the experimental steps carried out in the laboratory into a single monolithic device. This review will primarily focus on principles and techniques of LOC for detection of microbial nucleic acid in food and environment, including sample preparation, nucleic acid amplification and sample detection.